Survival strategies for people on the autism spectrum - Fleisher, Marc, 1967- (Jessica Kingsley Publishers, 2006)
Of contents and aims -- An overview of autism -- The worry of the 'what if?' scenario -- The vital role of communication -- The art of independent living -- Rules of socialising -- Further education and training survival guide -- The world of sport as an aid -- The challenge of sharing ideas with the wider audience -- Dealing with uncertainty -- Autism in a nutshell.